Does Functional Bracing of the Unstable Shoulder Improve Return to Play in Scholastic Athletes? Returning the Unstable Shoulder to Play. (January 2021) - Kwapisz, Adam; Shanley, Ellen; Momaya, Amit M.; Young, Chris; Kissenberth, Michael J.; Tolan, Stefan J.; Lonergan, Keith T.; Wyland, Douglas J.; Hawkins, Richard J.; Pill, Stephan G.; Tokish, John M.
Background: Functional bracing is often used as an adjunct to nonoperative treatment of anterior shoulder instability, but no study has evaluated the effectiveness of in-season bracing. The purpose of this study was to examine successful return to play in a nonoperative cohort of adolescent athletes with in-season shoulder instability and compare those athletes treated with bracing to those who were not. Hypothesis: The use of functional bracing will improve success rates in a cohort of athletes treated nonoperatively for in-season shoulder instability. Study Design: Cohort study. Level of Evidence: Level 3. Methods: A total of 97 athletes with anterior shoulder instability were followed for a minimum of 1 year. The mean age was 15.8 ± 1.4 years (range, 12.0-18.0 years). All athletes were treated with initial nonoperative management. Twenty athletes (21%) were also treated with bracing while 77 (79%) were not. The athlete completing the current season and 1 subsequent season without surgery or time lost from shoulder injury was defined as a successful outcome. Results: There was no statistical difference in nonoperative success rates between the braced and nonbraced athletes ( P = 0.33). Braced athletes (n = 20) returned to play 80% of the time, while nonbraced athletes (n = 77) returned at a rate of 88%. Of the braced athletes, 85% were football players (n = 17). A football-only comparison demonstrated no difference between braced failures (26%) and nonbraced failures (16%) ( P = 0.47). Conclusion: This is the first study to evaluate the utility of functional bracing in returning an athlete to sport and completing a full subsequent season without surgery or time loss due to injury of the shoulder. In adolescent athletes with shoulder instability treated nonoperatively, functional bracing did not result in increased success rates when compared with no bracing. Clinical Relevance: The data from this study indicate that functional bracing may not improve success rates for athletes with shoulder instability.